(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background Aging of the workforce poses a dramatic challenge for health and safety in all European countries. Method Our study was based on a comprehensive review of the literature on productive aging, work engagement, and human engineering, with particular reference to older worker issues. Results Productive aging, work engagement, and participatory ergonomics appear to be the most promising areas of research in the field of worker aging. An analysis of intervention programs enabled us to identify three main approaches that could be used to tackle the problem. These include encouraging older adults to be involved in work activities, enhancing their work engagement, and sustaining their productive efforts through participatory changes in the working environment and the promotion of healthy lifestyles. Occupational health and safety services in the workplace must extend their activities of prevention to encompass not only traditional environmental risk factors, but also non-occupational risk factors, so that this holistic approach promotes good practices and positive attitudes. Conclusions A set of recommendations and policy briefs for supra-national, national and local authorities was formulated.